INFLUENCE OF A WALK IN THE ACTIVITIES OF DAILY LIFE OF ELDERLY (Fiep Bulletin - online, 2013)
When discussing the interaction between physical activity and aging, two factors appear to currently be in the spotlight, they are the specificity and functionality. The specificity is related to the development of programs that meet the specific characteristics of a given population, and leverage significant adjustments to the different organ systems in health enhancement. Already functionality can be observed by the transfer of the positive effects arising from the exercise to the daily tasks of practitioners. The aim of this study was to evaluate the effects of a specific program of walking in elderly influence the activities of daily living. The program lasted 2 months with 4 sessions of practice per week and 60 minutes each. As measures were used to test and 6-minute walk test battery of ADL. The program was effective for all variables.
Keywords: ADL; Seniors; Training